Hypoelastic UR-free model for soils under cyclic loading. Issue 97 (June 2017) - Camões Lourenço, João; dos Santos, Jaime Alberto; Pinto, Pedro
Abstract: The study of problems that deal with soil behaviour under seismic loading conditions requires the use of a constitutive model able to reproduce the cyclic behaviour of soils from small strains to failure. Models commonly used when modelling soils at small to medium strain domain, for certain cyclic loading scenarios, are based on non-linear elasticity of the stress-strain relationship. These models have a group of rules to define first loading behaviour and to define unloading and reloading behaviour. Most models of this type rely on non-linear backbone functions and adopt Masing rule, having fixed formulas with a limited set of parameters, which are calibrated to adapt to experimental testing data. However, being these functions dependent on fixed formulas, makes them somewhat inflexible and hard to adapt to some experimental data. The objective of this work was the development of two simple but flexible non-linear elastic soil models that, given strain-dependent modulus and damping results from laboratory tests, could be easily calibrated: Hypoelastic spline based model and Hypoelastic UR-free model . The mathematical formulation is explained, the capability to describe peculiar soils behaviours is proved and an implementation in a FEM code is presented and discussed. Highlights: development of two simple but flexible non-linear elastic soil models for cyclic actions. explanation of mathematical formulation. proof of the capability to describe peculiar soils behaviours. implementation in a FEM code. calculation of a real site response.